Evolution of offshore dredge pits applications to the Black Sea - Samanacı, Arzu Gözde. (Thesis (M.S)-Bogazici University.Institute for Graduate Studies in Science and Engineering, 2005., 2005)
The present work investigates planform and profile evolutions of the dredge pits atthe inner shelf. The governing equations are derived from the Bailard & Inman (1981) bedload sediment transport equations, which are extended to account for the longshoregradients in the bathymetry caused by the dredge pit. The evolution of the pit isnumerically modeled with a set of unsteady, nonlinear, partial differential equations. Longtermnumerical test runs using a large range of wave and pit characteristics have lead to a number of dimensionless parameters, which control the fate of the dredge pit. The dredgepit is found to diffuse in the longshore and cross-shore directions at different backfillingrates, depending on wave and pit characteristics. The sensitivity analyses reveal that theUrsell number, relative wave length, and pit flatness control the half life of the pit. Under shore-normal waves, the dredging contour is found to diffuse symmetrically about thecenter of the pit. Under oblique waves, the pit migrates alongshore against the wave. Tosimulate long-term evolution of dredge pits under real field conditions, waves with varyingheight, period, angle and duration are used from statistics of the southwestern Black Sea. The half life of the backfilling is found to be on the order of decades, which is muchshorter than the half life computed using a monochromatic wave with the averagestatistical wave parameters for the entire simulation. This result indicates that most of thebackfilling occurs not during average wave conditions, but during seldom extreme waves.
Keywords: Geology, Structural.